2022
DOI: 10.1002/adfm.202111365
|View full text |Cite
|
Sign up to set email alerts
|

Operando Formation of Van der Waals Heterostructures for Achieving Macroscale Superlubricity on Engineering Rough and Worn Surfaces

Abstract: Macroscale superlubricity breakdown of lubricating materials caused by substrate surface roughening and mechanochemical modification poses great challenges for their practical tribological applications. Here, a facile way is reported to access robust macroscale superlubricity in a vacuum environment, via the operando formation of graphene/transition‐metal dichalcogenide (TMDC) heterostructures at wear‐induced rough surfaces. By trapping active amorphous carbon (a‐C) wear products between TMDC flakes, the sandw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 61 publications
0
31
0
Order By: Relevance
“…Combined with the incommensurate contact, the COF was greatly reduced to the superlubricity level. Macro-scale superlubricity can be also obtained through transitionmetal dichalcogenide nanoflake coating deposited on the amorphous carbon (a-C) substrate [81]. Load-driven graphitization of a-C wear products can be observed during the wear-in process, leading to the formation of van der Waals heterostructures and the realization of macro-scale superlubricity.…”
Section: Structural Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…Combined with the incommensurate contact, the COF was greatly reduced to the superlubricity level. Macro-scale superlubricity can be also obtained through transitionmetal dichalcogenide nanoflake coating deposited on the amorphous carbon (a-C) substrate [81]. Load-driven graphitization of a-C wear products can be observed during the wear-in process, leading to the formation of van der Waals heterostructures and the realization of macro-scale superlubricity.…”
Section: Structural Changesmentioning
confidence: 99%
“…At last, superlubricity can be more easily achieved through the synergetic effect with graphene-based materials and other nanomaterials. Previous literature suggested that the macro-scale superlubricity can be achieved by the in-situ formed nanoscrolls with graphene-based materials and nanoparticles [82,84,85] or the heterostructures containing graphene and other 2D materials [64,81,91]. Better environmental adaptivity can be also achieved through the synergetic effect between graphene-based materials and other nanomaterials [125,126].…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…[156] Fabricating protective coatings with high hardness, low friction coefficient and high wear resistance is one of the most effective strategies to reduce the friction and wear of rubbing surfaces. For example, diamond-like carbon (DLC), containing both sp 2 and sp 3 bonding [157] has its distinctive mechanical and physical properties (Figure 18b). MXenes are believed to be one of the state-of-the-art 2D nanomaterials regarding their tribological performance (Figure 18c).…”
Section: Introduction Of Designing Triboelectric Surfaces For Boostin...mentioning
confidence: 99%
“…With the development of advanced machines, the working conditions of machines become more and more complicated, due to extreme pressure, high temperature, irradiation [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ], etc. Friction and wear are the main reasons for the machine failure.…”
Section: Introductionmentioning
confidence: 99%